The time is ripe to investigate human centromeres by long-read sequencing. (5th October 2021) - Suzuki, Yuta; Morishita, Shinichi
Abstract: The complete sequencing of human centromeres, which are filled with highly repetitive elements, has long been challenging. In human centromeres, α-satellite monomers of about 171 bp in length are the basic repeating units, but α-satellite monomers constitute the higher-order repeat (HOR) units, and thousands of copies of highly homologous HOR units form large arrays, which have hampered sequence assembly of human centromeres. Because most HOR unit occurrences are covered by long reads of about 10 kb, the recent availability of much longer reads is expected to enable observation of individual HOR occurrences in terms of their single-nucleotide or structural variants. The time has come to examine the complete sequence of human centromeres.